KUALITAS PARTISIPASI PUBLIK: STUDI IMPLEMENTASI E-LEGISLASI DI BADAN PENGEMBANGAN HUKUM NASIONAL (BPHN) INDONESIA - Khusrini, Ari Khusrini; Kurniawan, Teguh (Universitas Gorontalo, 2019)
BPHN is one of the implementing subjects in the stages of national legislation, which has a portal is an interface for the public to actively participate in the formation of legislation. The purpose of this study was to analyze the quality of the implementation of public participation-based e-legislation at BPHN. This study uses qualitative data collection techniques using data period from 2016-2019. The study show that the quality of the implementation of e-legislation based on public participation not optimum yet, due to: (i) unpreparedness of the social environment; (ii) the less quality of the portal; (iii) institutional capacity and organization relations problems; (iv) unreadiness of e-rulemaking framework; and (v) system run without operational regulation base.